2009
DOI: 10.1176/ps.2009.60.6.831
|View full text |Cite
|
Sign up to set email alerts
|

Crisis Intervention Team Training and Special Weapons and Tactics Callouts in an Urban Police Department

Abstract: Although the CIT model may yield important benefits in other domains, this study found no evidence of declining SWAT utilization as the number of CIT-trained officers accrued. The absence of association is likely due to the relatively low prevalence of SWAT use and the very different nature of CIT versus SWAT responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Mental health training may improve how police officers respond to and record situations involving individuals with mental health problems [ 9 ]. A recent systematic review of the effectiveness of mental health training programmes for non-mental health trained professionals, including the police, reported that there were huge variations in training design, delivery and content, making the best approaches to training unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mental health training may improve how police officers respond to and record situations involving individuals with mental health problems [ 9 ]. A recent systematic review of the effectiveness of mental health training programmes for non-mental health trained professionals, including the police, reported that there were huge variations in training design, delivery and content, making the best approaches to training unclear.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Training and Education about Mental Illness for Police Organisations (TEMPO) [ 11 ] is being introduced into police forces in Canada and the Crisis Intervention Team (CIT) programme [ 12 ] is being introduced into police forces in the USA and elsewhere. In the UK, police forces are required to adhere to the CoP standards for mental health training provision, but have autonomy to decide how training is delivered and so the amount of training received varies across forces [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…While DuPont & Cochran (2000) have reported an association between CIT implementation in Memphis and decreased use of high-intensity police units such as Special Weapons and Tactics (SWAT) teams, Compton and colleagues (2009) did not find an association between CIT implementation and SWAT call outs (Compton, Demir, Oliva & Boyce, 2009). A few studies have examined CIT’s impact on use of force and injuries.…”
Section: Introductionmentioning
confidence: 99%
“…A hostage situation would be a typical example, as well as when a criminal barricades himself in a building, riots, and other high risk operations. (Avdija, 2014;Compton, Demir, Oliva, and Boyce, 2009;Snow, 1999Snow, , 1996. Because of the burden placed upon them by their unique responsibilities, S.W.A.T.…”
Section: Introductionmentioning
confidence: 99%